Gynocentric communication among nuclear kin in the USA and Spain - Brewer,Devon D (PeerJ Preprints, 2016)
Paternity uncertainty seems to have shaped humans' differential investment in kin. I examined sex differences in communication among nuclear kin to expand inquiry on this matter and address some methodological limitations in prior work. I analyzed data from national surveys in the USA and Spain and a study of mobile phone communication in the immediate aftermath of the 2013 Boston Marathon bombings. Respondents communicated mildly to moderately more with mother than father and more with sister than brother. The differences in communication with mother and father appeared in both subjective survey data and objective mobile telephone records. Across communication modes and studies, women and men did not differ consistently in overall frequency of communication. Matricentric and sororicentric tendencies were larger for the modes likely to involve dyadic communication (such as telelphone calling and texting) than modes which often involve communication in group settings (face-to-face). The tendency to communicate more with female than male kin also appeared to be stronger in women respondents than in men. These results are consistent with paternity uncertainty as an ultimate evolutionary cause of differential investment in kin.
Keywords: communication; sex differences; social networks